Beginning OS X Lion apps development - Privat, Michael (Books for professionals by professionals., 2011)
With the Mac App Store launch in early 2011, a new age in Mac development began. Look for many of the cool apps for iPhone and iPad coming to an iMac or MacBook Pro near you! Beginning OS X Lion Apps Development explains how to develop OS X Lion-based apps and publish them in the Mac App Store. It begins with the basics of Objective-C and Cocoa, and then moves through all the topics necessary to build and publish your first successful Mac apps!